Developing a method to sample potential resuspension of radioactive contaminants near the former Rocky Flats Technical Plant - Alcantar, Richard V., author; Sudowe, Ralf, advisor; Johnson, Tom, committee member; Volckens, John, committee member (Colorado State University. Libraries, 2024)
From 1952 until 1989, the Rocky Flats Technical Plant processed plutonium for use as triggers in nuclear weapons. Throughout the facility's nearly 37 years in operation, several events led to radioactive contamination in areas within and surrounding the site. Since then, multiple cleanup projects have occurred, remediating contamination to acceptable levels. However, an increase in the number, size, and severity of Colorado wildfires in recent years has raised public concern for the potential resuspension of radioactive surface contamination to the now-populous areas surrounding Rocky Flats. Air sampling during specific conditions such as high winds, naturally occurring wildfires, and controlled burns would provide valuable data to determine if resuspension of radioactive contamination may be of concern. Sampling under such circumstances, however, is restricted by situation, permission, and weather. Whereas traditional aerosol sampling collects "total dust" samples to amass particles in the air with equal efficiency, without regard to particle size fraction, the use of a cascade impactor to separate aerosols by size can be utilized to relate how deep varied-sized particles might penetrate the human respiratory tract after inhalation. This would not only indicate the presence of radionuclides but also the deposition location within the human body, an important factor in determining the best dose estimate for the person. This study will compare the efficacy of a 3D-printed cascade impactor in separating particle size fractions to the capability of a commercial Andersen cascade impactor. Methods used in this thesis included radiological analysis with a Mirion LB4200 gas proportional counter. Significant imperfections of a printed prototype indicate that a stage-to-stage comparison between a commercial and a 3D-printed cascade impactor cannot be justified. Additionally, it is unlikely that current technology is capable of printing the exact same impactor with each subsequent print. The determination of a similar decay curve between stages of both impactors in some instances as well as similar trends in activity fraction by filter, however, indicate that a functional 3D-printed cascade impactor is feasible. Individually, each printed cascade impactor would require proper characterization to determine the particle size fraction that each stage captures. The evidence outlined in this study suggests that a functional cascade impactor can be fabricated by 3D printing. Still, additional studies would be necessary to characterize particle size distribution properly.
Keywords: air sampling; Rocky Flats; 3D printer; wildfire; cascade impactor